مدى التزام شـــركة جود التجارية بالمسؤولية الاجتماعية "دراســـــة ميدانية" - قاسم, سامر; هبرة, لينا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت البحث إلى تحديد مدى التزام شركة جود التجارية بالمسؤولية الاجتماعية وفق المجالات الآتية: المسؤولية الاجتماعية تجاه كل من: المجتمع, والبيئة, والمراجعين, والعاملين, والمساهمين, والحكومة, والموردين, والمنافسين, وفئات المجتمع. اعتمد البحث على المنهج الوصفي, وشمل مجتمع البحث جميع العاملين في شركة جود التجارية, والبالغ عددهم (860) عاملاً وعاملة, وقد تمّ تحديد حجم العينة بالاعتماد على قانون العينة الإحصائي, حيث بلغ حجم العينة من العاملين (266) عاملاً وعاملة تمّ توزيع الاستبانات عليهم, وأعيد منها (231) استبانة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (86.84%). استخدمت الباحثة في معالجة البيانات البرنامج الإحصائي SPSS.23 معتمدة الأساليب الإحصائية المناسبة والتي تتمثل بـ: المتوسط الحسابي, الانحراف المعياري, الأهمية النسبية, اختبار الوسط الحسابي. اختبار t)) لعينة واحدة, وكان من أهم نتائج البحث أنّ الشركة محل الدراسة تلتزم بالمسؤولية الاجتماعية وفق مجالاتها الآنفة الذكر وبدرجة كبيرة. The study aimed at determining the extent of the company's commitment to social responsibility according to the following areas: Social responsibility towards: community, environment, auditors, employees, shareholders, government, suppliers, competitors, The study was based on the Descriptive Methodology. The research society included all the employees of Joud Trading Company, which numbered (860) workers and workers. The sample size was determined by the statistical sample law. The sample size was 266 workers, (231) complete and valid for statistical analysis, with a response rate of (86.84%). The researcher used data processing SPSS.23, which is based on the following statistical methods: arithmetic average, standard deviation, relative importance, arithmetic mean. Test t) for one sample. One of the most important results of the study is that the company in question is committed to social responsibility according to the aforementioned fields and to a large extent.